2011
DOI: 10.1242/dev.060269
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking in mouse oocytes requires transient F-actin meshwork destabilization

Abstract: Female meiotic divisions are extremely asymmetric, giving rise to a large oocyte and small degenerating polar bodies, keeping the maternal stores for further embryo development. This asymmetry is achieved via off-center positioning of the division spindle. Mouse oocytes have developed a formin-2-dependent actin-based spindle positioning mechanism that allows the meiotic spindle to migrate towards the closest cortex. Using spinning disk microscopy and FRAP analysis, we studied the changes in the organization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 27 publications
6
62
0
Order By: Relevance
“…Actin transcript levels have been observed to decrease in this manner during meiotic maturation of human oocytes (Steuerwald et al, 2001). Tubulin protein levels fluctuate during meiosis I, increasing at GVB and MI stages, and then decreasing in MII (Figure 1C, D), as has been observed (Azoury et al, 2011). Thus, anillin transcript and protein are present during meiotic maturation of the mouse oocyte.…”
Section: Resultssupporting
confidence: 78%
“…Actin transcript levels have been observed to decrease in this manner during meiotic maturation of human oocytes (Steuerwald et al, 2001). Tubulin protein levels fluctuate during meiosis I, increasing at GVB and MI stages, and then decreasing in MII (Figure 1C, D), as has been observed (Azoury et al, 2011). Thus, anillin transcript and protein are present during meiotic maturation of the mouse oocyte.…”
Section: Resultssupporting
confidence: 78%
“…who showed that the changes in density and dynamics of actin filaments were concomitant with the increase in nuclear permeability just before GVBD 45 . Luo et al .…”
Section: Discussionmentioning
confidence: 98%
“…Compared with the cytoplasmic actin mesh in oocytes, which undergoes rapid polymerization and depolymerization, [22][23][24] cortical actin remains relatively stable during oocyte maturation, except for the formation of the cortical actin cap in the region toward which the spindle approaches.…”
Section: Overexpression Of Constitutively Active Cofilin (Ca-cofilin)mentioning
confidence: 99%